2021
DOI: 10.3389/fneur.2021.783365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Frequency Repetitive Transcranial Magnetic Stimulation on Upper Limb Dystonia in Patients With Wilson's Disease: A Randomized Controlled Trial

Abstract: Background: Upper limb dystonia is a frequent complication of Wilson's disease (WD). It can lead to poor quality of life and disability. Currently, no effective treatment for it exists. Therefore, we carried out a clinical trial to determine whether high frequency repetitive transcranial magnetic stimulation (rTMS) on the primary motor cortex alleviates upper limb dystonia in WD patients.Methods: This study was a single-center, double-blind, randomized clinical study, included 60 WD patients with upper limb dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…A total 642 participants were included across 51 studies, with ages ranging from 7 to 79 years ( M = 46.24, SD = 12.29). Four studies included patients with acquired dystonia, associated with Wilson’s disease 46 , 47 or cerebral palsy. 48 , 49 Twenty-two studies included participants who were not on oral medications (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total 642 participants were included across 51 studies, with ages ranging from 7 to 79 years ( M = 46.24, SD = 12.29). Four studies included patients with acquired dystonia, associated with Wilson’s disease 46 , 47 or cerebral palsy. 48 , 49 Twenty-two studies included participants who were not on oral medications (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…A single study applied tACS, 50 and one applied high-frequency (10 Hz) rTMS. 46 Dystonia-specific motor training, kinesiotherapy or biofeedback was employed concurrently with NIBS in eight studies. 32 , 33 , 35 , 36 , 51 54 All study designs, participant demographics and characteristics are provided in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, these findings may be helpful for the clinical treatment of WD patients with dystonia. Previous studies have found that transcrania magnetic stimulation (TMS) can be used to alleviate and treat some neuropsychiatric disorders and Wilson's disease [30,54]. Other studies have also demonstrated that the dorsolateral prefrontal cortex and cerebellum can serve as targets to treat depression [55,56] and schizophrenia [57,58], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the abnormal tension of the biceps brachii and medialis and lateralis gastrocnemius muscle is one of the commonly involved parts of extremities dystonia and can also reveal the degree of dystonia in upper and lower limbs, which can be indirectly reflected by measuring the muscle tension levels of biceps brachii and gastrocnemius muscle [22][23][24][25]. Furthermore, previous dystonia-related studies and our recent dystonia study of WD have shown that the digital muscle function assessment system (MyotonPRO) can reliably assess the degree of extremities dystonia by measuring the muscle tension levels of the biceps brachii and gastrocnemius [26][27][28][29][30]. Therefore, we selected the extremities to measure the biomechanical level of WD patients, and the muscle biomechanical level was assessed using the MyotonPRO by measuring the biceps brachii and medialis and lateralis gastrocnemius muscle on both sides to reflect the degree of dystonia.…”
Section: Clinical and Muscle Biomechanical Assessmentmentioning
confidence: 99%